Chicagoin and around the loop - Wolfe Gerard R. (MC Graw Hill, 2004)
The series of walking tours of downtown Chicago begins at the corner of Michigan Avenue and congress Parkway, with a visit to the Auditorium Building; it then continues west to the canyons of Chicago's financial district and explores many old and new buildings that have given Chicago the unique reputation as the cradle of modern architecture